PENGARUH PEMBERIAN PUPUK NPK DAN VOLUME AIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI (Capsicum annum L) - wirman, Adi; Yetti, Husna; ', Syahroni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Chili is really needed to complete comsumption of family needs and industrial fabrics. The biggest problem low production in the cultivation of chili’s in Riau isthe land conversion and lack of proper cultivation technique. One way to increase productionin the cultivation of chili’s withfertilizing and giving water with right doses, right way and the right timeincreasesproduction of chili plants.The objective of the research was to determine the bestinteraction of giving NPK fertilizerand water volumeof growth and production of chili plants.This research was conducted at Gauze House the Technical Service Unit of the Faculty Agriculture from Mey to October2014.This research arranged experimentally using Completely Randomized Design (CRD), which consists of 2 factors.The first factor is the NPK fertilizer consists of 3 levels: NPK fertilizer dose of0.625 g/plant, NPK fertilizer dose of 1.25 g/plant and NPK fertilizer dose of 1.875 g/plant. The second factor is the giving water volume consists of 3 levels: water volume of 0,5 liter/plant, water volume of 1 liter/plant and water volume of 1,5 liter/plant. From two factors, then obtained 9 combined treatments. So that acquired 27 units of the experiment, each experimental unit consisted of 5 and take 3 samples, plant, so there were 135 samples plant. Observation parameters were plant height, flowering date, dichotomous height, stem diameter, crown width, fruit length, fruit diameter, harvest quantity, fruit weight per plant. The research result showed that the treatment of giving NPK fertilizer to increase where height plant, flowering date, crown width, harvest quantity and fruit weight per plant. Giving water volume on increase plantheight, flowering date, stem diameter, crown width and fruit weight per plant. Giving NPK fertilizer dose 1,25 gr/plant with water volume 1,5 liter is the best treatment interactionof height plant, stem diameter, crown width, fruit diameter, harvest quantity and fruit weight per plant. Keyword: Chili, NPK fertilizer, Giving Water volume.